MAP selection-diversity DFE for indoor wireless data communications. - Yumin Lee (IEEE Journal on selected areas in communications)
Indoor high-speed wireless data networks encounter signal fading and delay-spread multipath propagation. Hence, the realization of low error rate transmission requires measures to combat the performance degradation due to both signal fading and intersymbol interference (ISI). Receiver diversity has been known to be an efficient way of coping with the former problem, while adaptive equalization could be used to mitigate the effects of the latter. Incorporation of receiver diversity with adaptive equalization is therefore desirable. We propose a novel selection-diversity approach with an adaptive decision-feedback equalizer (DFE). In this method, selection is done on a symbol-by-symbol basis such that the output of the branch with the lowest estimated a posteriori probability of error is used as the final decision. This final (and hence more reliable) decision is used to adapt the DFE for all diversity branches. It is shown in this paper that the proposed selection rule is optimal for selection-diversity in the maximum a posteriori probability (MAP) sense. A very simple selection metric can be derived from this selection rule and practical ways of computing the selection metric are also presented. Simulation results show that the proposed method is very efficient. It is capable of achieving almost the same performance as an optimal [least squares (LS)], but computationally intensive, combining diversity approach. Furthermore, at an average bit error rate (BER) of 10-4, a gain of approximately 1.25 dB can be achieved over a previously proposed selection-diversity equalization approach